COFFEE COMMODITY FOR THE WELFARE OF THE COMMUNITIES IN TEMANGGUNG DISTRICT - Fatmawati Sungkawaningrum; Prasetyo Hestina Anggraini (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
Coffee is one of the world's commodities. The economic cycle in the community can be a transaction activity. The types of coffee that stand out are Arabica coffee and Robusta coffee. The flow of coffee farming forms a link in many fields in it. Community members who are involved in coffee farming activities start from upstream to downstream procurement. Seed farmers produce and continue to develop good types of coffee seeds in the hope of producing superior quality coffee. Business actors in the field of manure milling, traders of agricultural facilities and fertilizer manufacturers also play a role in the coffee development cycle. In picking coffee beans, farmers learn from generation to generation and make field observations. Consult with modern agricultural experts to obtain the level of effectiveness and cost efficiency. The marketing of selected coffee beans is carried out with a good pattern so that it will produce the aroma and taste that characterizes Temanggung coffee products. It is hoped that the role of the government can help the level of welfare of Temanggung coffee farmers to introduce a wider range of coffee products, so that Temanggung coffee products have more marketability, higher economic value and are sustainable. Creating people who have purchasing power so that the production flow can be better rotated